Nebulized corticosteroids versus systemic corticosteroids for patients with acute exacerbation of chronic obstructive pulmonary disease: A systematic review and meta-analysis comparing the benefits and harms reported by observational studies and randomized controlled trials - Hu, Han-Shuo; Wang, Zhuo; Zhao, Li-Mei; Liu, Xiao-Dong (Frontiers in Pharmacology, 2022)
Objective: Systematic comparison of the efficacy and safety of nebulized corticosteroids and systemic corticosteroids for treating acute exacerbation of chronic obstructive pulmonary disease reported by high-quality, real-world observational studies and randomized controlled trials. Methods: MEDLINE, EMBASE, and Cochrane Library databases were searched from the database creation date to April 1, 2022. Eligible observational studies and randomized controlled trials with changes in lung function and blood gas analysis results as the primary endpoints of interest, and the numbers of deteriorations and adverse events as the secondary endpoints were sought. Results: Of the 2,837 identified studies, 22 were eligible and included in our analysis (N = 5,764 patients). Compared with systemic corticosteroids, nebulized corticosteroids resulted in comparable improvements in predicted FEV1%, FEV1, PaO2, PaCO2, and SaO2 at the treatment endpoint; however, observational studies reported more significant treatment outcomes with nebulized corticosteroids for FEV1 (mean difference, 0.26; 95% confidence interval [CI], 0.17¬-0.35; p < 0.005). In terms of adverse reactions, the risks of gastrointestinal symptoms were 11% (Log risk ratio [LogRR]=0.10; 95% CI, 0.05-0.15; p < 0.005) higher for systemic corticosteroids than for nebulized corticosteroids in randomized controlled trials, while the risks of hyperglycemia were 6% (LogRR=0.06; 95% CI, 0.01-0.11; p = 0.01) and 13% (LogRR=0.12; 95% CI, 0.09-0.16; p < 0.005) higher in observational studies and randomized controlled trials, respectively. Conclusion: According to our meta-analysis, either study type supported that nebulized corticosteroids can be used as an alternative to systemic corticosteroids for treating acute exacerbation of the chronic obstructive pulmonary disease. However, more well-designed prospective studies are needed to determine the optimal dose of nebulized corticosteroids and the advantages of sequential therapy.